Cortical Inhibition State-Dependent iTBS Induced Neural Plasticity - Diao, Xiaoying; Lu, Qian; Qiao, Lei; Gong, Youhui; Lu, Xiao; Feng, Min; Su, Panpan; Shen, Ying; Yuan, Ti-Fei; He, Chuan (Frontiers in Neuroscience, 2022)
Background Intermittent theta burst stimulation (iTBS) is an effective stimulus for long-term potentiation (LTP)-like plasticity. However, iTBS-induced effects varied greatly between individuals. Ample evidence suggested that an initial decrease in local γ-aminobutyric acid (GABA) or enhancement in N-methyl-D-aspartate (NMDA) facilitation neurotransmission is of vital importance for allowing LTP-like plasticity to occur. Therefore, we aimed to investigate whether the individual level of GABA or NMDA receptor-mediated activity before stimulation is correlated with the after-effect in cortical excitability induced by iTBS. Methods Fifteen healthy volunteers were recruited for the present study. We measured short-interval intracortical inhibitory (SICI), long-interval intracortical inhibitory (LICI), and intracortical facilitation (ICF), which index GABAA receptor-, GABAB receptor-, and glutamate receptor-mediated activity, respectively, in the cortex before conducting iTBS. After iTBS intervention, the changes of motor-evoked potential (MEP) amplitude were taken as a measure for cortical excitability in response to iTBS protocol. Results There was a significant negative correlation between the amount of SICI measured before iTBS and the after-effect of iTBS-induced LTP-like plasticity at the time points of 5, 10, and 15 min after inducing iTBS. A multiple linear regression model indicated that SICI was a good predictor of the after-effect in cortical excitability induced by iTBS at 5, 10, and 15 min following stimulation. Conclusion The present study found that GABAA receptor-mediated activity measured before stimulation is negatively correlated with the after-effect of cortical excitability induced by iTBS. SICI, as the index of GABAA receptor-mediated activity measured before stimulation, might be a good predictor of iTBS-induced LTP-like plasticity for a period lasting 15 min following stimulation.